Security Sector Reform and Implementation of Good Governance: A Theoretical Study - Sarjito, Aris; Yin Chhao Rath (Faculty of Social and Political Science, 2024)
Security Sector Reform (SSR) is critical for ensuring long-term stability, particularly in post-conflict and transitioning states. The integration of good governance principles—such as transparency, accountability, rule of law, and public participation—plays a key role in the success of SSR efforts. This study aims to examine how these governance principles can be effectively incorporated into SSR processes. Using a qualitative research approach, this study analyzes secondary data, including existing literature and case studies from Sierra Leone, Afghanistan, and Bosnia and Herzegovina. The research findings highlight that SSR is more successful when it is locally driven, adapted to the specific political and cultural context, and supported by strong governance institutions. In Sierra Leone, the integration of good governance was critical for reform success, while in Afghanistan, weak governance and political resistance hindered SSR progress. The study concludes that local ownership, political will, and robust institutional frameworks are essential for the effectiveness of SSR. Future research should explore innovative models that prioritize local ownership and adapt governance principles to the unique dynamics of individual states. Additionally, studies that investigate the long-term impact of SSR in diverse contexts would provide actionable insights for enhancing reform strategies.